Clinical case of chemoresistant tuberculosis in the patient with tuberous sclerosis: difficulties of diagnosis, features of the course and treatment. - N. S. Kolesnik; N. A. Marchenko; A. I. Stadnik; V. V. Ielisieiev; T. A. Stepanova (Medičnì Perspektivi)
In the practical activities of a modern doctor, significant difficulties are noted in the diagnostics and proper management of patients with hereditary diseases due to the limited coverage of the population by genetic researches. For a long time, the patients with a variety of complaints are observed by doctors of various specialties, and the therapy often has little effect due to a lack of understanding of the true causes of pathological changes. The situation is complicated by case of a combined course of a hereditarily caused disease and some other disease of an infectious, non-infectious or tumor nature. The aim of the research was to study the characteristics of clinical manifestations, course of tuberculosis with resistance to anti-TB drugs in a patient with a rare hereditary disease from the group of phacomotoses - Bourneville-Pringle disease or tuberous sclerosis. This disease has a wide range of clinical manifestations, accompanied with the development of benign neoplasms in various organs and systems, damages to the skin, brain, organs of vision, lungs, kidneys, heart, as well as the musculoskeletal and endocrine system. It leads to development of various infectious and non-infectious pathologies in these organs. The article covers a 4-year period of observation of a young patient with late diagnosed tuberous sclerosis, suffering from pulmonary tuberculosis and tuberculosis of urinary system, includes the initial diagnosis of a specific disease, the course, the dynamics against received treatment and the development of relapse with the formation of resistance to anti-TB drugs. The difficulties in the management of tuberculosis in this patient were in the detection of numerous neoplasms and changes in the internal organs, in particular in the kidneys and lungs, which characterized tuberous sclerosis, on the one hand this contributed to untimely diagnosis of tuberculosis, and on the other hand – worsening the course and the progression of a specific process, as well as an unfavourable prognosis for recovery.